Growth in Egg Yolk Enhances Salmonella Enteritidis Colonization and Virulence in a Mouse Model of Human Colitis. - Matthew R Moreau; Dona Saumya S Wijetunge; Megan L Bailey; Sudharsan R Gongati; Laura L Goodfield; Eranda Mangala K Kurundu Hewage; Mary J Kennett; Christine Fedorchuk; Yury V Ivanov; Jessica E Linder; Bhushan M Jayarao; Subhashinie Kariyawasam (PLoS ONE)
Salmonella Enteritidis (SE) is one of the most common causes of bacterial food-borne illnesses in the world. Despite the SE's ability to colonize and infect a wide-range of host, the most common source of infection continues to be the consumption of contaminated shell eggs and egg-based products. To date, the role of the source of SE infection has not been studied as it relates to SE pathogenesis and resulting disease. Using a streptomycin-treated mouse model of human colitis, this study examined the virulence of SE grown in egg yolk and Luria Bertani (LB) broth, and mouse feces collected from mice experimentally infected with SEE1 (SEE1 passed through mice). Primary observations revealed that the mice infected with SE grown in egg yolk displayed greater illness and disease markers than those infected with SE passed through mice or grown in LB broth. Furthermore, the SE grown in egg yolk achieved higher rates of colonization in the mouse intestines and extra-intestinal organs of infected mice than the SE from LB broth or mouse feces. Our results here indicate that the source of SE infection may contribute to the overall pathogenesis of SE in a second host. These results also suggest that reservoir-pathogen dynamics may be critical for SE's ability to establish colonization and priming for virulence potential.